(3GdCShGb GdOhdjI (B:s (3GdeaGgje hGdfXQjGJ hGdSjGSGJ (B/s - (3TjMI, eUWai QTOjs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s)
(3GdJYQja Heaghe GdShb GdOhdjI heXGgQ GdYhdeI GdGbJUGOjI,eaghe GdShb GdOhdjI,XQha fTCI GdShb GdOhdjI,ehVhYGJ GdShb GdOhdjI,GdEWQGa GdeJYGedI aj GdShb GdOhdjI,NUGFU GdShb GdOhdjI hJfXjeGJg hhXGFag,GdfXQjGJ GdeaSQI ddJLGQI HGdCShGb GdOhdjI,GdfXQjI GdJbdjOjI(B((3GdeRGjG GdeWdbI(B)(3,GdfXQjI GdJbdjOjI (B((3GdeRGjG GdfSHjI(B)(3,JaSjQgPg GdfXQjI dbjGe GdJLGQI GdOhdjI ef NdGd GdGSJNOGe GdCeKd ddehGQO,GdfXQjI GdJbdjOjI(B((3GdWH GdeJHGOd(B)(3,GdfXQjI GdQGgfI aj YHGQGJ fbOjI,MOhO GdfXQjI GdJbdjOjI,GdfXQjI GdfjhcdGSjcjI,GdfXQjI GdMOjKI dJaSjQ GdJLGQI GdOhdjI(B((3GdfXQjI GdShjOjI(B)(3,GdSjGSGJ GdJLGQjI GdehLgI ddCShGb GdOhdjI,SjGSGJ MQjI GdJLGQI,GdSjGSGJ GdJLGQjI ddOhd GdfGejI,GdSjGSGJ GdJLGQjI ddOhd GdeJbOeIs
(3HHdjhZQGajG GdaUd GdChd U(B.56(3;HHdjhZQGajG GdaUd GdKGfj U(B.128(3; HHdjhZQGajG GdaUd GdKGdK U(B.187s
Keywords: (3GdCShGb GdeGdjIs; (3GdJLGQI GdNGQLjIs